2005
DOI: 10.1016/j.ejcts.2004.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin treatment is associated with an increased apoptosis rate in experimental vein grafts☆

Abstract: We conclude that treatment of experimental vein grafts with rapamycin is associated with an increased apoptosis rate in the vascular wall and a trend towards reduction of neointimal hyperplasia. These results suggest that apoptosis may be a beneficial antiproliferative component for the treatment of vein graft disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…This observation is also in agreement with previous studies [56]. Previously, decreased levels of anti-apoptotic proteins through inhibition of nuclear translocation of NF-KB protein [57] or by activation of Fas and Fas ligand pathway have been suggested as the most likely mechanisms by which sirolimus increases apoptosis in endothelial cells and vascular smooth muscle cells [58].…”
Section: Discussionsupporting
confidence: 91%
“…This observation is also in agreement with previous studies [56]. Previously, decreased levels of anti-apoptotic proteins through inhibition of nuclear translocation of NF-KB protein [57] or by activation of Fas and Fas ligand pathway have been suggested as the most likely mechanisms by which sirolimus increases apoptosis in endothelial cells and vascular smooth muscle cells [58].…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that CCI-779 induces apoptosis, which is consistent with the higher levels of cleaved caspase-9 found in CCI-779-treated tumors. Others have also reported that rapamycin or CCI-779 may exert an antitumor effect by inducing apoptosis (El-Hashemite et al, 2004;Frost et al, 2004;Avellino et al, 2005;Kenerson et al, 2005;Schachner et al, 2005). The fact that the IFN-g-treated tumors did not exhibit more apoptosis than untreated tumors is puzzling, given our observations of elevated cleaved caspases in these tumors.…”
Section: Discussionmentioning
confidence: 51%
“…Daemen 28 showed that inhibition of apoptosis prevents inflammation and tissue injury and that a monocyte chemoattractant, EMAP-II, is the molecule linking apoptosis and inflammation. Sirolimus, although possibly increasing apoptosis rate in vein grafts, 29 at the same time lowers the expression of EMAP-II in SM cells, reducing their adhesiveness for monocytes and preventing local inflammation. 26 …”
Section: P R E V E N T I O N O F R E S T E N O S I Smentioning
confidence: 97%